Psychosocial risk assessment in Hospital. - Brescia, Filomena; Mazzeo, Gabriella (Rivista di Psicologia Clinica, 2013)
This paper proposes a psychosocial risk assessment case in a hospital in Rome, according to the criteria provided by the Work Health and Safety Act. Those involved in the assessment may comply with the rule without caring about the client request, the management and employees’ expectations, the usability of the results. For a psychologist this means moving from producing documents to activating interest and development in the context of intervention. The article analyzes two social representations of the employee, conveyed by the work health and safety act: as a person with specific motivations that negotiates the rules in the workplace or as a physically and mentally vulnerable individual. This determines different visions of the assessment: analysis of the organizational relationships or diagnosis of individual malfunctions. We will analyze the assessment process developed with the protection and risk prevention Service responsible in the hospital: the relation between the consulting function and the technical one in the Service, how to enable the hospital strategic management, the coordinators and the 2000 employees’ participation. The results of the research show significant levels of risk linked to the conflict with the strategic management, to the pressure made by patients and their relatives, to the health workers’ lived experience of isolation despite complaints to the magistrates, thus showing the limits of defensive medicine. Then we present the training work with the first aid and emergency service workers carried out with the aim of intervening on the high level of risk noticed and on the sentinel events linked to the aggressions within that unit.